Environment-friendly biaxial orientation super-heat-sealing polyester film and preparation method thereof

Through the biaxially oriented ultra-thermal sealable polyester film, combined with the design of the core layer and the heat-sealable layer, the problems of low recovery rate and insufficient sealing strength of multi-layer food packaging materials are solved, and high sealing strength and environmentally friendly packaging are achieved Production of materials.

CN119451813APending Publication Date: 2025-02-14ESTER IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480002884.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-08
Filing Date
2024-02-08
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing multi-layer flexible food packaging materials have low recovery rates and are difficult to achieve high seal strength and environmental protection during manufacturing.

Method used

A biaxially oriented ultra-thermal sealable polyester film was developed to prepare films with high seal strength and environmental protection characteristics through a combination of core layer and heat-sealable layer, using coextrusion process and biaxial tensile technology.

Benefits of technology

It achieves high sealing strength, low moisture and oxygen transmittance, and can be sealed at lower temperatures, reducing the environmental impact of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168994030000301
    Figure BDA0005168994030000301
  • Figure BDA0005168994030000311
    Figure BDA0005168994030000311
  • Figure BDA0005168994030000312
    Figure BDA0005168994030000312
Patent Text Reader

Abstract

There is provided a biaxially oriented super heat sealable polyester film comprising: a core layer comprising polyethylene terephthalate, post consumer recovery grade polyethylene terephthalate, and a filler; and a heat sealable layer disposed on at least one surface of the core layer and comprising a copolyester composition; wherein the copolyester composition of the heat-sealable layer comprises terephthalic acid, dimethyl terephthalate or a combination thereof; at least one diol selected from the group consisting of monoethylene glycol, diethylene glycol, triethylene glycol, 1, 3-propanediol, 1, 4-butanediol, neopentyl glycol, hexanediol and cyclohexanedimethanol; and isophthalic acid; wherein the biaxially oriented super heat sealable polyester film exhibits a sealing strength of greater than 800 gmf / inch when sealed at a pressure of 4 kg / cm2 at 140 DEG C for 1 second.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This PCT application claims the benefit of priority to Indian Patent Application No. 202311008051 filed on February 8, 2023, the entire disclosure of which is incorporated herein by reference for any and all purposes. Technical Field

[0003] The present disclosure relates to compositions and methods for making environmentally friendly, super heat sealable, biaxially oriented super heat sealable polyester films or laminates having seal through contamination, low temperature sealing and high seal strength. The present disclosure also relates to heat sealable copolyesters for producing super heat sealable biaxially oriented super heat sealable polyester films and the use of the films as packaging materials. Background Art

[0004] It is known that manufacturing polymers from recycled content reduces energy consumption by approximately 70% and emits fewer greenhouse gases, significantly reducing the environmental impact of these types of food packaging. But historically, recycling rates for films have been problematic because these materials are often multi-layered or include more polymorphs and are more challenging to collect than other food packaging such as glass, aluminum and steel. The United Nations has adopted 17 sustainable goals, one of which is climate change. To benefit the climate and a better environment, manufacturers of multi-layer flexible food packaging face the burden of redesigning the packaging material in a way that it can be recycled.

[0005] Multi-material multilayer structures / packaging consist of more than one layer of different materials, where the components are layered to form flexible packaging (bags, bags, shrink films, other flexible products) or rigid packaging (trays, cups, containers, other rigid plastic sheets). This type of packaging is widely used in the FMCG (fast-moving consumer goods) industry for items with low cost prices and short service life, such as beverages, food and toiletries. Packaging for fresh food may consist of four to seven layers of different components. A wide range of substances with different physical and chemical properties form multi-material multilayers. Various polymers are applied, such as polyolefins PE (polyethylene) and PP (polypropylene) and their chemical variants HDPE (high-density polyethylene), LDPE (low-density polyethylene), LLDPE (linear low-density polyethylene), OPP (oriented polypropylene) and CPP (cast polypropylene), or polyesters such as PET (polyethylene terephthalate) and PBT (polybutylene terephthalate). These multi-layer multi-material films and sheets are developed by coextrusion or lamination technology. In multi-material multilayer packaging, the use of different materials in different layers is associated with functional and packaging performance requirements. Since protecting goods from abrasion, moisture, oxygen, light, odor, taste and chemicals is critical to packaging performance, effective flexible barrier packaging solutions are needed to achieve these goals.

[0006] Replacing multi-layer flexible barrier packaging is challenging because there are only a limited number of barriers available. Therefore, the environmentally friendly super heat sealable biaxially oriented polyester film produced in the present invention will provide solutions to most of the problems associated with the packaging industry. Summary of the invention

[0007] The embodiments described herein generally relate to biaxially oriented super heat sealable polyester films or laminates. In one aspect, a biaxially oriented super heat sealable polyester film is provided comprising a core layer and a heat sealable layer. In some embodiments, the core layer comprises polyethylene terephthalate, post-consumer recycled grade polyethylene terephthalate, and a filler. In other embodiments, the heat sealable layer is disposed on at least one surface of the core layer and comprises a copolyester composition. In some embodiments, the copolyester composition of the heat sealable layer comprises (a) terephthalic acid, dimethyl terephthalate, or a combination thereof; (b) at least one diol selected from monoethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, hexanediol, and cyclohexanedimethanol; and (c) isophthalic acid. In some embodiments, the biaxially oriented super heat sealable polyester film is heated to 4 kg / cm2 at 140°C. 2 The seal strength is greater than 800 gmf / inch when the pressure seal is sealed for 1 second.

[0008] In some embodiments, the biaxially oriented super heat sealable polyester film of the present technology has at least two layers. In another embodiment, the heat sealable copolyester comprises (a) 35 to 75 weight percent of terephthalic acid, dimethyl terephthalate, or a combination thereof; (b) 25 to 40 weight percent of at least one glycol selected from monoethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, hexanediol, and cyclohexanedimethanol; and (c) 10 to 30 weight percent of isophthalic acid. In yet another embodiment, the core layer mixture comprises 40 to 80 weight percent of polyethylene terephthalate polyester; 0 to 30 weight percent of modified polyethylene terephthalate polyester, which is a fiber grade polyester; 20 to 100 weight percent of post-consumer recycled polyethylene terephthalate; and 0.05 to 0.1 weight percent of silica. In some embodiments, the polyethylene terephthalate polyester of the core layer mixture comprises about 70 to 80 weight percent terephthalic acid, about 22 to 30 weight percent monoethylene glycol, and about 0.5 to 5 weight percent diethylene glycol. In other embodiments, the fiber-grade polyester of the core layer mixture comprises about 68 to 85 weight percent terephthalic acid, about 20 to 30 weight percent monoethylene glycol, and about 2 to 10 weight percent diethylene glycol.

[0009] In some embodiments, the biaxially oriented super heat sealable polyester film of the present technology has a total thickness of about 15 μm to about 50 μm, wherein the core layer accounts for about 50% to about 80% of the total thickness of the film. In other embodiments, the biaxially oriented super heat sealable polyester film of the present technology has one or more of the following: when heated to 4 kg / cm at 140°C, the film has a thickness of about 100 μm to about 50 μm, and the core layer accounts for about 50% to about 80% of the total thickness of the film. 2 The seal strength of the film at a pressure seal of 1 second is about 800 gmf / inch to about 4500 gmf / inch; the total thickness is about 15 μm to about 50 μm, wherein the core layer accounts for about 50% to about 80% of the total thickness of the film; the shrinkage measured according to ASTM D1204 after treatment with hot air at 150°C for 30 minutes is about 2% or less in each of the longitudinal and width directions; the puncture resistance measured according to ASTM F1306 is about 5.5 N or more; the tensile strength at break measured according to ASTM D882 is about 1300 kg / cm 2 About 1900kg / cm 2 ; and an elongation at break of about 100 kg / cm2 as measured according to ASTM D882 2 About 160kg / cm 2 In some embodiments, the biaxially oriented super heat sealable polyester film has a weight of 0.30 to 45 g / m 2 - Water vapor transmission rate in the range of 0.40 to 100 cc / m 2 - Day-range oxygen transfer rates.

[0010] In some embodiments, the biaxially oriented super heat sealable polyester films of the present technology further comprise one or more additional layers selected from sealant layers, print layers, metal layers, barrier layers, adhesive layers, coating layers, primer layers, and protective layers.

[0011] In another aspect, a multilayer high barrier film is provided, which includes a biaxially oriented super heat sealable polyester film of the present technology. In some embodiments of the multilayer film, a barrier layer is disposed on at least one of the one or more core layers. In some embodiments, the barrier layer comprises at least one of ethylene vinyl alcohol copolymers, polyvinyl alcohol polymers and copolymers, or polyvinylidene chloride, aluminum, silicon oxide, and aluminum oxide; in some embodiments, the multilayer high barrier film is unprinted or reverse printed. In some embodiments, the multilayer high barrier film has a thickness of 0.30 to 0.40 g / m 2 - Water vapor transmission rate in the range of 0.40 to 0.50 cc / m 2 - Day range of oxygen transmission rate. In one aspect, a biaxially oriented super heat sealable polyester film or multilayer high barrier film is provided for use in a bag or overwrap packaging.

[0012] In one aspect, a copolyester composition is provided, comprising a first polymer composition comprising pure terephthalic acid, ethylene glycol and isophthalic acid; and a second polymer composition comprising pure terephthalic acid, ethylene glycol and neopentyl glycol. In some embodiments, the weight ratio of the first polymer composition to the second polymer composition is in the range of about 70:30.

[0013] The embodiments described herein are generally directed to methods for providing environmentally friendly super heat sealable, biaxially oriented polyester films with seal through contamination, low temperature sealing, and high seal strength. In one aspect, a method for preparing a biaxially oriented polyethylene terephthalate super heat sealable film is provided. The method includes preparing a core layer mixture comprising polyethylene terephthalate, modified polyethylene terephthalate, post-consumer recycled polyester, and a filler, wherein the modified polyethylene terephthalate comprises a fiber-grade polyester; preparing a heat sealable layer mixture comprising a heat sealable copolyester; loading the core layer mixture into a main extruder to obtain a molten first mixture; loading the heat sealable layer mixture into a sub-extruder to obtain a molten second mixture; extruding the molten first mixture and the molten second mixture through a die to provide an unstretched film; and and biaxially stretching the unstretched film under preheating conditions and heat treating the film to a temperature of about 250° C. to about 290° C., so that the stretching ratio in the longitudinal direction is about 3 to about 3.6 times based on the original length of the unstretched film, and the stretching ratio in the transverse direction is about 3.2 to about 4.5 times based on the original width of the unstretched film; cooling the stretched film to obtain a biaxially oriented super heat sealable polyethylene terephthalate film; wherein the heat sealing temperature of the biaxially oriented super heat sealable polyethylene terephthalate film is about 100° C. to about 200° C. In some embodiments, the biaxially oriented super heat sealable polyester film of the present technology has at least two layers.

[0014] In some embodiments, the preparation of the heat-sealable layer mixture includes charging terephthalic acid, dimethyl terephthalate or a combination thereof with at least one diol and isophthalic acid into a reactor to obtain a reaction mixture; subjecting the reaction mixture to an esterification reaction at a temperature of about 240° C. to about 270° C. to obtain an esterified prepolymer; charging the esterified prepolymer into a polycondensation reactor and adding one or more polycondensation catalysts selected from silica, antimony compounds and magnesium compounds; subjecting the prepolymer to a polycondensation reaction at a temperature in the range of about 270° C. to about 310° C. to obtain a molten amorphous polymer; cooling and processing the molten polymer to form chips or pellets; and optionally subjecting the obtained chips to solid-state polymerization to obtain a heat-sealable layer mixture comprising a heat-sealable copolyester having an intrinsic viscosity greater than 0.65 dL / g.

[0015] In some embodiments of the methods of the present technology, the heat-sealable copolyester comprises about 35 to about 70 weight percent terephthalic acid, dimethyl terephthalate, or a combination thereof; about 21 weight percent to about 40 weight percent monoethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, hexanediol, cyclohexanedimethanol, or a mixture of any two or more thereof; and about 10 weight percent to about 30 weight percent isophthalic acid. In some embodiments of the methods of the present technology, the core layer mixture comprises about 40 weight percent to about 80 weight percent polyethylene terephthalate polyester; about 0 weight percent to about 30 weight percent fiber-grade polyester; about 20 weight percent to about 100 weight percent post-consumer recycled polyethylene terephthalate; and about 0.05 weight percent to about 0.1 weight percent silica. In some embodiments of the methods of the present technology, the polyethylene terephthalate polyester of the core layer mixture comprises about 70 wt % to about 85 wt % terephthalic acid, about 20 wt % to about 30 wt % monoethylene glycol, and about 0.5 wt % to about 5 wt % diethylene glycol. In some embodiments of the methods of the present technology, the fiber-grade polyester of the core layer mixture comprises about 65 wt % to about 85 wt % terephthalic acid, about 20 wt % to about 30 wt % monoethylene glycol, and about 2 wt % to about 10 wt % diethylene glycol.

[0016] In some embodiments of the method of the present technology, the method further comprises passing the molten first mixture and the molten second mixture through a filter. In some embodiments, the method further comprises laminating the molten first mixture and the molten second mixture together in a feed-block to produce a laminated molten structure in an extrusion die.

[0017] In some embodiments of the methods of the present technology, the processing step includes one or more steps of preheating, stretching, and cooling the extruded structure. In some embodiments, stretching is performed sequentially or simultaneously in the machine direction and the transverse direction. In some embodiments, preheating, stretching, and cooling include machine direction preheating, stretching, and cooling, followed by transverse direction preheating, stretching, and cooling. In some embodiments, the preheating conditions include passing the unstretched film through a machine direction preheating zone at a temperature of about 70°C to about 90°C, stretching the preheated structure in the longitudinal direction, and passing the longitudinally stretched film through a machine direction cooling zone at a temperature of about 70°C to about 90°C.

[0018] In some embodiments of the method of the present technology, the method further comprises passing the cooled longitudinally stretched film through a transverse direction preheating zone at a temperature of about 92°C to about 110°C, stretching the preheated film in the transverse direction, and passing the transversely stretched film through a machine direction cooling zone at a temperature of about 60°C to about 85°C. In some embodiments of the method of the present technology, the method further comprises adding an additional layer to the biaxially oriented super heat sealable polyester film. In some embodiments, the additional layer comprises one or more of a sealant layer, a print layer, a metal layer, a barrier layer, an adhesive layer, a coating, a primer layer, and a protective layer.

[0019] In another aspect, a packaging material is provided, which includes a biaxially oriented super heat sealable polyester film of the present technology. In yet another aspect, a packaging material is provided, which includes a biaxially oriented super heat sealable polyester film produced by the method of the present technology. In some embodiments, the film includes a food grade packaging film or a medical product packaging film.

[0020] In another aspect, a method for preparing a heat-sealable copolyester composition is provided, and the heat-sealable copolyester composition is used to prepare the film of the present technology. In some embodiments, the method for preparing the heat-sealable copolyester composition includes charging terephthalic acid, dimethyl terephthalate or a combination thereof with at least one diol and isophthalic acid into a reactor to obtain a reaction mixture; subjecting the reaction mixture to an esterification reaction at a temperature of about 240°C to about 270°C to obtain an esterified prepolymer; charging the prepolymer into a polycondensation reactor and adding one or more polycondensation catalysts selected from silica, antimony compounds and magnesium compounds; subjecting the prepolymer to a polycondensation reaction at a temperature in the range of about 270°C to about 310°C to obtain a molten amorphous polymer; crystallizing the amorphous polymer at a temperature in the range of about 110°C to about 170°C to obtain chips or pellets having a crystallinity of about 40% or more; and optionally subjecting the chips or pellets to solid-state polymerization to obtain a heat-sealable layer mixture comprising a heat-sealable copolyester having an intrinsic viscosity greater than 0.65 dL / g. In some embodiments of the method, the copolyester composition comprises a first polymer composition comprising pure terephthalic acid, ethylene glycol, and isophthalic acid and a second polymer composition comprising pure terephthalic acid, ethylene glycol, and neopentyl glycol, wherein the weight ratio of the first polymer composition to the second polymer composition is in the range of about 70:30.

[0021] It should be understood that all combinations of the aforementioned concepts and the additional concepts discussed in more detail below (provided that such concepts are not mutually inconsistent) are considered to be part of the subject matter disclosed herein. All combinations of the claimed subject matter appearing at the end of this disclosure are considered to be part of the subject matter disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a flow chart of a method for manufacturing a biaxially oriented super heat-sealable polyester film according to one embodiment of the present technology.

[0023] Figure 2 is an illustration of a packaging material having a single layer of surface printed flexible recyclable PET film according to one embodiment of the present technology.

[0024] Figure 3 is an illustration of a packaging material having a single layer of surface metallized flexible recyclable PET film according to one embodiment of the present technology.

[0025] Figure 4 is an illustration of a packaging material having multiple layers of reverse printed or unprinted flexible recyclable PET film according to one embodiment of the present technology.

[0026] Figure 5 is an illustration of a packaging material having a multi-layer, high barrier coated, reverse printed or unprinted flexible recyclable PET film according to one embodiment of the present technology.

[0027] Figure 6 is an illustration of a packaging material having a multi-layer, ultra-high barrier coated, reverse printed or unprinted flexible recyclable PET film according to one embodiment of the present technology. DETAILED DESCRIPTION

[0028] Various embodiments are described below. It should be noted that the specific embodiments are not intended as an exhaustive description or as a limitation to the broader aspects discussed herein. An aspect described in conjunction with a specific embodiment is not necessarily limited to that embodiment, but can be practiced with any other one or more embodiments.

[0029] For convenience, before further describing the present invention, certain terms used in the specification, examples and appended claims are collected here. These definitions should be read in conjunction with the rest of this disclosure and should be understood by those skilled in the art. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art.

[0030] As used herein, "about" will be understood by one of ordinary skill in the art and will vary to some extent depending on the context in which it is used. If there is a use of the term that is unclear to one of ordinary skill in the art in the context in which the term is used, "about" will mean up to plus or minus 10% of the particular term.

[0031] Unless otherwise noted herein or clearly contradictory to the context, the use of the terms "a / an" and "said" and similar indicators in the context of describing an element (especially in the context of the accompanying claims) should be understood to cover both the singular and the plural. Unless otherwise noted herein, the enumeration of the range of values ​​herein is intended only to be used as a shorthand for individually referring to each individual value falling within the range, and each individual value is incorporated into the specification as if it is individually mentioned herein. Unless otherwise noted herein or clearly contradictory to the context, all methods described herein can be performed in any suitable order. Unless otherwise noted, the use of any and all examples or exemplary language (such as "such as") provided herein is intended only to better illustrate the embodiment and is not intended to limit the scope of the claims. Any language in the specification should not be interpreted as indicating that any unclaimed element is necessary.

[0032] The term "including" is used to mean "including, but not limited to." "Including" and "including, but not limited to" are used interchangeably.

[0033] The term "polyester" generally refers to the esterification or reaction product between a polybasic organic acid and a polyol. The present disclosure is particularly directed to a class of polyesters referred to herein as polyethylene terephthalate, in which terephthalic acid is used as the polybasic organic acid, and particularly to PET, but it should be understood that the present disclosure is by no means limited to PET. It encompasses all polyesters, namely PET, PBT, PTT and their related copolyester blends and alloys.

[0034] As used herein, the term "copolymer" refers to a blend of PET and PBT / PTT in any desired ratio.

[0035] As used herein, the term "core layer" or "outer layer" is a relative term and is not necessarily a surface layer. Instead, these terms refer to a layer comprising the outer surface of a film or product or alternatively a core surface of a laminated film or product.

[0036] The terms "heat sealable layer" and "sealant layer" are used interchangeably to refer to an "inner layer," which refers to a layer comprising the inner surface of a film or product. For example, the inner layer forms the inner surface of a package, which may be adjacent to or in contact with a packaged product.

[0037] As used herein, the term "super heat sealable" refers to a polymeric material that can be sealed to itself or to another material by the application of heat and pressure.

[0038] As used herein, the term "high barrier" refers to a material that has been subjected to a barrier coating process and exhibits superior resistance compared to standard or untreated materials. This improved barrier capability makes the coated material suitable for use in MAP (modified atmosphere packaging) applications requiring stringent protective measures, including but not limited to food packaging, pharmaceuticals or electronic components.

[0039] As used herein, the term "ultra-high barrier" refers to a metallized film or laminate that provides superior performance compared to standard metallized or non-metallized films. This improved barrier capability is particularly valuable in applications where a very strong protective barrier is required for the preservation of the package contents. In industries such as food packaging, pharmaceuticals, and electronics, where maintaining product integrity is critical, ultra-high barrier materials are often used to ensure extended shelf life and optimal quality of packaged items.

[0040] Ratio, concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is used only for convenience and brevity, and should be flexibly interpreted as not only including the numerical value clearly listed as range limit, but also including all individual numerical values ​​or sub-ranges contained in the range, as each numerical value and sub-range are clearly listed.For example, 5 to 40 mol % should be interpreted as not only including the limit of 5 to 40 mol % clearly listed, but also including sub-ranges, such as 10 mol % to 30 mol %, 7 mol % to 25 mol %, etc., and the individual amount in the specified range, including fractional amount, such as 15.5 mol %, 29.1 mol % and 12.9 mol %.

[0041] The use of the expression "at least" or "at least one" indicates the use of one or more elements or components or amounts, as such use may achieve one or more desired objectives or results in embodiments of the present disclosure.

[0042] Any discussion of documents, acts, materials, devices, articles of manufacture etc. included in this specification is solely for the purpose of providing a context for the present disclosure. It should not be taken as an admission that any or all of these matters form part of the prior art base or are common general knowledge in the field relevant to the present disclosure as they existed anywhere before the priority date of this application.

[0043] Although this article emphasizes the specific features of the present disclosure, it should be understood that various modifications can be made, and many changes can be made to the preferred embodiments without departing from the principles of the present disclosure. From the disclosure herein, these and other modifications of the nature of the present disclosure or the preferred embodiments will be obvious to those skilled in the art, and it should be clearly understood that the foregoing descriptive matters should only be interpreted as an explanation of the present disclosure rather than a limitation.

[0044] In one aspect, an environmentally friendly, super heat sealable, biaxially oriented polyester film and laminate are provided, which have reduced seal contamination, low temperature sealing and high seal strength. Ultra-high seal strength is a feature of the sealing process, which results in very strong and reliable bonding between packaging materials, which is produced by a combination of carefully selected materials, controlled sealing conditions and appropriate sealant compositions. The film has good mechanical strength, moisture and oxygen barrier properties, excellent dimensional stability, easy processability, good bag breakage resistance and chemical resistance, and can be easily mechanically or chemically recycled. In addition, the film has good orientation and pullability, and has excellent longitudinal and transverse orientation capabilities without breaking during its production process. These properties are achieved via a coextruded biaxially oriented polyester film, which includes components such as polyethylene terephthalate (PET), PET recycled after consumption, isophthalic acid (IPA), 2,2-dimethylpropane-1,3-diol (NPG) and optionally CHDM (cyclohexanedimethanol).

[0045] The biaxially oriented super heat sealable polyester film may comprise a monolayer structure having a single layer or a multilayer structure having at least two layers, wherein the at least two layers include, for example, two layers, three layers, four layers, five layers, six layers, seven layers, eight layers, nine layers or ten layers. The biaxially oriented super heat sealable polyester film has an outer layer (core layer) and an inner layer (heat sealable layer or sealant layer). The heat sealable layer is disposed on at least one surface of the core layer. In the case of two layers, it may be a layered core layer / heat sealable layer, and in the case of three layers, it may be a heat sealable layer / core layer / heat sealable layer, and the like.

[0046] Biaxially oriented super heat sealable polyester film can be manufactured into various thickness ranges. The thickness of biaxially oriented super heat sealable polyester film (for example, when the film has two layers of super heat sealable films) can be in the range of about 5 μm to about 60 μm, including about 10 μm to about 55 μm, about 15 μm to about 50 μm, about 18 μm to about 45 μm, about 20 μm to about 40 μm or about 25 μm to about 30 μm. In some embodiments, super heat sealable polyester film can be laminated, in which case, the thickness of the laminated film can be in the range of about 5 μm to about 100 μm, including about 8 μm to about 90 μm, about 10 μm to about 80 μm, about 15 μm to about 75 μm, about 20 μm to about 70 μm or about 25 μm to about 60 μm. In some embodiments, the total thickness of biaxially oriented super heat sealable polyester film can be about 15 μm to about 50 μm.

[0047] The core layer and the heat sealable layer can each have the same thickness or different thicknesses. The thickness of the heat sealable layer can be about 20% to about 40% of the total film thickness, including about 22% to about 38%, about 25% to about 35% or about 28% to about 32%. For example, with respect to a 30 μm thick film, the heat sealable layer thickness can be about 9 to about 15 μm. The thickness of the outer layer can be about 60% to about 80% of the total film thickness, including about 62% to about 78%, about 65% to about 75% or about 68% to about 72%. For example, with respect to a 30 μm thick film, the outer layer thickness can be about 15 to about 24 μm. In some embodiments, the biaxially oriented super heat sealable polyester film can have a total thickness of about 15 μm to about 50 μm, wherein the core layer accounts for about 50% to about 80% of the total thickness of the film. In some embodiments, the thickness ratio of the core layer to the heat-sealable layer may be about 50:50, including from about 60:40, about 65:35, about 70:30, about 75:25, about 80:20, or about 85:15.

[0048] The inner layer is a heat sealable layer or sealant layer of the film, which provides sealing strength to the film. The sealant layer provides heat sealing of the film to itself or to another film or non-film layer, thereby facilitating low temperature sealing of the film and providing low seal contamination. Heat sealing can be achieved using one or more of a wide range of sealing methods, including but not limited to heat sealing, hot air sealing, hot wire sealing, ultrasonic sealing, infrared radiation sealing, ultraviolet radiation sealing, electron beam sealing, bead sealing, impulse sealing, etc.

[0049] The inner layer, which is a heat sealable layer or sealant layer, is formed by a polyester composition, typically a copolyester composition formed by a dicarboxylic acid-diol reaction. The copolyester composition comprises a dicarboxylic acid or a dicarboxylic acid ester, such as terephthalic acid (PTA) and / or dimethyl terephthalate (DMT). In some embodiments, the copolyester composition comprises purified dicarboxylic acids and / or purified dicarboxylic acid esters. In some embodiments, the copolyester composition comprises purified PTA and / or purified DMT as a major component. In some embodiments, PTA and / or DMT alone or in combination account for about 20% to about 90% of the total weight of the copolyester composition, including about 25% to about 80%, about 30% to about 65%, about 35% to about 70%, about 40% to about 60%, or about 45% to about 55% of the total weight of the copolyester composition.

[0050] The copolyester composition of the heat sealable layer may also include one or more minor copolymer components, such as glycols and additional dicarboxylic acids. Suitable additional dicarboxylic acids include, but are not limited to, isophthalic acid (IPA), adipic acid, sebacic acid, naphthalene dicarboxylic acid, 4,4-diphenyl dicarboxylic acid and derivatives thereof. In some embodiments, the additional dicarboxylic acids include purified dicarboxylic acids. In some embodiments, the additional dicarboxylic acids include IPA or purified IPA. In some embodiments, the additional dicarboxylic acids account for about 1% to about 50% of the total weight of the copolyester composition, including about 5% to about 40%, about 10% to about 30%, about 15% to about 25%, or about 20% to about 25% of the total weight of the copolyester composition.

[0051] The copolyester composition of the heat sealable layer may also include one or more glycols. Suitable glycols may include, but are not limited to, monoethylene glycol / ethylene glycol (MEG / EG), diethylene glycol (DEG), triethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, neopentyl glycol (NPG), hexylene glycol, cyclohexanedimethanol or any combination of two or more thereof. Other glycols may also be added, including polyoxyalkylene glycols, such as polyethylene glycol and polypropylene glycol. In some embodiments, the copolyester composition includes one or more glycols selected from MEG, DEG and NPG. In some embodiments, the one or more glycols account for about 10% to 50% by weight of the gross weight of the copolyester composition, including about 20% to about 45%, about 25% to about 40% or about 30% to about 35%.

[0052] The heat-sealable copolyester may comprise, for example, (a) 35 to 75 weight percent of terephthalic acid, dimethyl terephthalate, or a combination thereof; (b) 25 to 40 weight percent of at least one diol selected from monoethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, hexanediol, and cyclohexanedimethanol; and (c) 10 to 30 weight percent of isophthalic acid.

[0053] The sealant layer may include a copolyester of PTA or DMT and IPA and one or more glycols such as MEG and NPG. In some embodiments, based on 100 wt % of the total weight of the copolyester, the PTA or DMT content may be about 30 wt % to 70 wt %, the glycol content is about 20 wt % to 65 wt %, the isophthalic acid content is about 5 wt % to 35 wt %, and the neopentyl glycol content is about 0 wt % to 10 wt %. In some embodiments, the sealant layer (copolyester) composition comprises about 35 wt % to about 60 wt % PTA or DMT, preferably PTA; about 25 wt % to about 40 wt % monoethylene glycol / ethylene glycol (MEG / EG), diethylene glycol (DEG), 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, or a mixture of any two or more thereof, preferably wherein the diol is MEG, DEG, neopentyl glycol, or a mixture of two or more thereof; about 10 wt % to about 30 wt % IPA; and about 1 wt % to about 5 wt % NPG.

[0054] In some embodiments, a copolyester composition is provided, comprising a first polymer composition comprising pure terephthalic acid, ethylene glycol, and isophthalic acid; and a second polymer composition comprising pure terephthalic acid, ethylene glycol, and neopentyl glycol; wherein the weight ratio of the first polymer composition to the second polymer composition is in the range of about 70:30.

[0055] The outer layer may be the core layer of the film, which provides structural strength to the film. The outer layer together with the inner layer provides a film with good mechanical strength, moisture and oxygen barrier properties, excellent dimensional stability, easy processing, good resistance to bag breakage and chemical resistance. The film is also easy to recycle mechanically or chemically.

[0056] The outer layer as the core layer may include various thermoplastic materials, for example, PET materials. Thermoplastic materials can be used in various available forms, including but not limited to powders, pellets, fragments, particles, flakes, blocks, beads, cylinders, rods, fluff, dust, etc. or combinations thereof. In some embodiments, the outer layer includes one or more virgin thermoplastic materials, recycled thermoplastic materials, and thermoformable grade thermoplastic materials. In some embodiments, the outer layer includes one or more virgin polyester materials, recycled polyester materials, and thermoformable grade polyester materials. In some embodiments, virgin polyester includes virgin PET as the main component. In some embodiments, recycled polyester includes post-consumer recycled PET as the main component. In some embodiments, thermoformable grade polyester includes thermoformable grade PET as the main component. In some embodiments, the outer layer composition includes one or more of PET (polyethylene terephthalate) polyester, FGT (thermoformable grade) polyester, and PCR (post-consumer recycled) PET.

[0057] In some embodiments, the outer layer comprises virgin PET. In some embodiments, the virgin PET accounts for about 20% to about 90% by weight of the outer layer composition, including about 25% to about 80% by weight, about 30% to about 70% by weight, about 35% to about 65% by weight, about 40% to about 60% by weight, or about 45% to about 55% of the total weight of the copolyester composition. The virgin PET can be formed by PTA and one or more diols such as EG and DEG. In some embodiments, based on 100% by weight of the total weight of the virgin PET, the PTA content can be about 40% to 80% by weight, the EG content can be about 10% to 40% by weight, and the DEG content can be about 0% to 10% by weight.

[0058] The outer layer composition may also include one or more thermoformable polyester materials, such as thermoformable PET. In some embodiments, the thermoformable PET accounts for about 5% to about 50% by weight of the outer layer composition, including about 5% to about 40% by weight, about 10% to about 30% by weight, about 15% to about 25% by weight, or about 20% to about 25% by weight of the outer layer composition. The thermoformable PET may be formed by PTA and one or more diols such as EG and DEG. In some embodiments, based on 100% by weight of the total weight of the thermoformable PET, the PTA content may be about 40% to 80% by weight, the EG content may be about 10% to 40% by weight, and the DEG content may be about 2% to 15% by weight.

[0059] The outer layer composition also includes post-consumer recycled PET. In some embodiments, PCR PET accounts for about 5% to about 60% by weight of the outer layer composition, including about 10% to about 50% by weight, about 15% to about 45% by weight, about 20% to about 40% by weight, about 15% to about 30% by weight, or about 20% to about 25% by weight of the outer layer composition. In some embodiments, the outer layer of the film may include 100% by weight of PCR PET. In another embodiment, the outer layer of the film may include less than 100% by weight, less than 99% by weight, less than 95% by weight, less than 90% by weight, less than 80% by weight, less than 70% by weight, or less than 60% by weight of PCR PET. In yet another embodiment, the outer layer of the film may include more than 5%, more than 10%, more than 15%, more than 20%, more than 30%, more than 40% by weight, or more than 50% by weight of PCR PET. In another embodiment, the amount of PCR PET in the entire film may range from about 10 wt % to about 90 wt %, about 20 wt % to about 80 wt %, about 25 wt % to about 75 wt %, or about 30 wt % to about 60 wt % of the total composition.

[0060] The outer layer can also include a variety of filler materials. Suitable filler materials can include but are not limited to silicon dioxide, titanium dioxide, cerium dioxide, aluminum hydroxide, magnesium hydroxide, aluminum oxide, magnesium oxide, boron oxide, calcium oxide, calcium carbonate, barium carbonate, lithium phosphate, calcium phosphate, magnesium phosphate, calcium sulfate, barium sulfate, talcum, clay or any combination of two or more thereof. In some embodiments, the filler material comprises or is silicon dioxide (silica). In some embodiments, based on the outer layer gross weight of 100 wt %, the filler material content can exist with about 0 wt % to 10 wt %, including about 0.0001 wt % to about 5 wt %, about 0.01 wt % to about 4 wt %, about 0.075 wt % to about 3 wt %, about 0.05 wt % to about 2 wt % or about 0.1 wt % to about 1 wt % of the outer layer composition. In some embodiments, the amount of silicon dioxide can be about 250ppm to about 2000ppm, including about 500ppm to about 1500ppm or about 750ppm to about 1000ppm.

[0061] In some embodiments, the outer layer (core) composition may include about 40 wt% to about 60 wt% polyester, wherein the polyester includes PET (73.5 wt% PTA, 25 wt% EG, and 1.5 wt% DEG); about 10 wt% to about 30 wt% FGT polyester, wherein the FGT polyester (71 wt% PTA, 23 wt% EG, and 6.0 wt% DEG); and about 20 wt% to about 40 wt% post-consumer recycled PET chips.

[0062] In some embodiments, the core layer mixture may include, for example, 40 to 80 weight percent polyethylene terephthalate polyester; about 0 to about 30 weight percent modified polyethylene terephthalate polyester, which is a fiber-grade polyester; about 20 to about 100 weight percent post-consumer recycled polyethylene terephthalate; and about 0.05 to about 0.1 weight percent silica. In some embodiments, the polyethylene terephthalate polyester of the core layer mixture comprises about 70 to 80 weight percent terephthalic acid, about 22 to 30 weight percent monoethylene glycol, and about 0.5 to 5 weight percent diethylene glycol. In some embodiments, the fiber-grade polyester of the core layer mixture comprises about 68 to 85 weight percent terephthalic acid, about 20 to 30 weight percent monoethylene glycol, and about 2 to 10 weight percent diethylene glycol.

[0063] The PET material of the inner layer and / or the outer layer may also contain other inorganic residues. Examples of such inorganic residues may include, but are not limited to, alkaline earth metal salts, alkali metal salts, including calcium, magnesium, sodium and potassium salts, antimony-containing compounds, germanium-containing compounds, titanium-containing compounds, cobalt-containing compounds, tin-containing compounds, aluminum, aluminum salts, phosphorus-containing compounds and anions, sulfur-containing compounds and anions, etc. or combinations thereof. The total amount of such inorganic residues may be from about 0 ppm to 1000 ppm, including from about 5 to 800 ppm, from about 10 to 700 ppm, from about 50 to 500 ppm, or from about 100 to 250 ppm.

[0064] The biaxially oriented super heat sealable polyester film of the present technology is environmentally friendly and has reduced seal pass contamination, low temperature sealing and high seal strength. For example, the film using a higher percentage of PCR fragments will help reduce the CO2 footprint. In some embodiments, the film of the present technology has a seal strength greater than about 500gmf / inch (gram force / square inch), preferably greater than about 800gmf / inch. In some embodiments, when heated at 4kg / cm at 140°C, the seal strength is greater than about 500gmf / inch (gram force / square inch). 2 The films of the present technology have a seal strength of about 800 gmf / inch to about 4500 gmf / inch, about 900 gmf / inch to about 4300 gmf / inch, about 1000 gmf / inch to about 4000 gmf / inch, or about 1100 gmf / inch to about 3800 gmf / inch when sealed with a pressure of 1 second.

[0065] The biaxially oriented super heat sealable polyester film of the present technology may have a shrinkage measured according to ASTM D1204 after being treated with hot air at 150° C. for 30 minutes of about 5% or less, about 4% or less, about 3% or less, about 2% or less, about 1.5% or less, or about 1% or less in each of the longitudinal and width directions.

[0066] The biaxially oriented super heat sealable polyester film may exhibit a puncture resistance of about 5.0 N or greater (including about 5.5 N or greater, about 6.0 N or greater, or about 6.5 or greater) and about 7.5 N or less (including about 7.0 N or less, or about 6.5 or less) as measured according to ASTM F1306. The biaxially oriented super heat sealable polyester film may exhibit a puncture resistance of about 5.5 N to about 7.0 N. In some embodiments, the biaxially oriented super heat sealable polyester film exhibits a puncture resistance of about 5.5 N or greater as measured according to ASTM F1306.

[0067] The biaxially oriented super heat sealable polyester film of the present technology can have a heat resistance of about 1000 kg / cm 2 About 2500kg / cm 2 Tensile strength at break, including about 1200kg / cm2 About 2200kg / cm 2 , about 1300kg / cm 2 About 1900kg / cm 2 or about 1500kg / cm 2 About 1800kg / cm 2 In some embodiments, the biaxially oriented super heat sealable polyester film of the present technology may have a heat resistance of about 1300 kg / cm 2 About 1900kg / cm 2 Tensile strength at break.

[0068] According to ASTM D882, the biaxially oriented super heat sealable polyester film of the present technology can have a heat resistance of about 80 kg / cm 2 About 220kg / cm 2 Elongation at break, including about 90kg / cm 2 About 200kg / cm 2 , about 100kg / cm 2 About 160kg / cm 2 or about 120kg / cm 2 About 160kg / cm 2 In some embodiments, the biaxially oriented super heat sealable polyester film of the present technology may have a heat resistance of about 100 kg / cm 2 About 160kg / cm 2 In some embodiments, the film may exhibit an elongation of about 140% or more, including about 100% or more, about 120% or more, about 140% or more, about 160% or more, about 180% or more, about 190% or more, about 200% or more.

[0069] The biaxially oriented super heat sealable polyester film of the present technology can have a thickness of about 0.10 to 50 g / m 2 - Water vapor transmission rate in the range of about 0.30 to 45 g / m 2 -day, about 0.50 to 40g / m 2 -day or about 0.80 to 35g / m 2 -day. The biaxially oriented super heat sealable polyester film of the present technology may have a heat resistance of about 0.20 to 150 cc / m 2 - Oxygen delivery rates in the range of about 0.30 to 125 cc / m 2 -Daily, about 0.40 to 100cc / m 2 -Daily, about 0.50 to 80cc / m 2 -day or 0.80 to 60cc / m 2-day. In some embodiments, the biaxially oriented super heat sealable polyester film of the present technology may have a weight of 0.30 to 45 g / m 2 - Water vapor transmission rate in the range of 0.40 to 100 cc / m 2 - Day-range oxygen transfer rates.

[0070] In another aspect, a method for manufacturing a super heat sealable biaxially oriented film is provided. In some embodiments, a conventional sequential biaxial orientation machine with a single screw main line extrusion and a twin screw sub-extrusion process can be used to prepare a super heat sealable biaxially oriented polyester film. For example, PET and modified PET pellets can be fed into the main extrusion line with a silica combination, and a blend of copolymerized PET pellets can be fed into the sub-extruder at the same time. The materials can be co-extruded, or they can be melted separately and then laminated together in a feed block to produce a molten structure in an extrusion die. Then, the laminated molten structure (for example, a PET sheet extruded from a slit die) can be quenched by means of a quenched casting drum to produce a thick and amorphous film. Subsequently, an electric heater roller group can be utilized to stretch the amorphous film along the longitudinal direction (MD) of the film or the length direction axis within a suitable temperature range. Stretching can be carried out in a system with a main extrusion line and a sub-extrusion line, so that the main extrusion line mixture and the sub-extruder mixture are extruded through a die head to shape, form or extrude the BOPET material into a desired structure. The die is tailored to the specific requirements of BOPET film production and will ensure the uniformity and precision of the final product. The die design allows complex and consistent shapes with high repeatability to be produced. Casting of extrudates is a manufacturing technique for shaping and solidifying molten BOPET materials into a desired form. In this process, the molten material is carefully passed through, where it solidifies and takes on the desired shape. Casting is particularly useful for producing complex pieces with intricate details, which contributes to the flexibility and adaptability of the BOPET film manufacturing process. In some embodiments, the uneven web is processed by cutting edges without stretching and stretching. In some embodiments, a thin layer of metal is deposited on the film substrate to produce a high moisture and oxygen barrier. The processed BOPET film is cut into finished products according to the required specifications or requirements.

[0071] refer to Figure 1A process flow chart is provided, which provides a method for producing a biaxially oriented polyester film. The method for producing a biaxially stretched polyester film can be carried out using a conventional sequential biaxial orientation machine with a main line extrusion and a sub-extrusion (coextrusion) process. PET chips are prepared to feed into the main extrusion line. PET chips can be prepared by crystallizing PET using a crystallizer during the manufacturing process to induce controlled crystallinity in the molten PET. A crystallinity of about 40% to about 50% or more can be targeted. This controlled crystallization will promote the formation of a structured crystalline matrix within the polymer. The crystallization temperature can be from about 120°C to about 200°C, including from about 150°C to about 180°C, from about 160°C to about 175°C, or from about 160°C to about 170°C. The result is enhanced mechanical strength, dimensional stability, and barrier properties of the film.

[0072] After the crystallization process, the PET chips are dried in a dryer to eliminate residual moisture. The dryer can use hot air to efficiently evaporate the water content, thereby ensuring that the finished product reaches the desired moisture level. The crystallization temperature can be from about 130°C to about 200°C, including from about 150°C to about 180°C, from about 160°C to about 175°C, or from about 165°C to about 170°C. The drying step can be performed for an appropriate time until the desired moisture level is reached. For example, drying can be performed to reduce the moisture from about 2000 ppm to about 40 to 60 ppm. This step helps to achieve uniform film quality, physical properties, and optical clarity.

[0073] The dried PET chips are introduced into a vacuum hopper, which will facilitate controlled feeding and metering of the PET resin into the main extruder. Applying a vacuum to the hopper will ensure consistent and uniform flow of the polymer material, thereby providing consistent film thickness and performance. The PET, thermoforming grade PET pellets, and post-consumer recycled polyester chips in the hopper (optionally in combination with a filler having the desired properties) are fed to the main extrusion line at a suitable temperature to obtain a first mixture. The melt temperature in the main extrusion line may be from about 150°C to about 350°C, including from about 180°C to about 320°C, from about 200°C to about 310°C, from about 230°C to about 300°C, or from about 255°C to about 280°C.

[0074] The coextrusion or sub-extrusion line feeds the contents of the inner layer (i.e., the copolyester of the PET layer and IPA, NPG and / or CHDM) to a process at a suitable temperature to obtain a second mixture. The melt temperature in the coextrusion line can be from about 150°C to about 350°C, including from about 180°C to about 320°C, 200°C to about 310°C, 250°C to about 300°C, or 260°C to about 280°C.

[0075] This extrusion process allows the material to be melted respectively, and then the first molten mixture polymer passes through a filter, and the filter helps to refine and purify the raw materials or fluids used in the manufacturing process. By effectively removing impurities and pollutants, the filter will ensure the integrity of the final BOPET film. This enhances the quality of the film by preventing defects and maintaining consistent material composition. Therefore, in some embodiments, the method of the present technology also includes passing the first molten mixture and the second molten mixture through a filter. In other embodiments, the method of the present technology also includes laminating the first molten mixture and the second molten mixture together in a feed block to produce a laminated molten structure in an extrusion die. The first mixture of step (a) and the second mixture of step (b) are laminated together in a feed block to produce a laminated molten structure and extruded by a die to shape, form or extrude the BOPET material into a desired structure.

[0076] The melt of the first and second mixtures is formed into a flat melt film in a multilayer die, and they are stacked. Subsequently, the multilayer film is pulled out and solidified with a chill roll and optionally a die of other rollers. The biaxial stretching of the film can be carried out individually, sequentially or simultaneously. In some embodiments, the biaxial stretching of the film is carried out sequentially. In other embodiments, the biaxial stretching of the film is carried out simultaneously. In sequential stretching, it is possible to first stretch in the longitudinal direction (that is, along the machine direction) and then stretch in the transverse direction (that is, along the orthogonal direction of the machine direction or at right angles to the machine direction). Alternatively, the opposite order can be used. The die of two rollers rotating at different speeds can be used to carry out the stretching in the longitudinal direction according to the required stretch ratio. For transverse stretching, a suitable tenter frame is used.

[0077] In some embodiments, the thermoplastic film may be first stretched in the longitudinal or machine direction, such that the thermoplastic film is preheated by a plurality of preheating rollers and then stretched in the longitudinal direction using the peripheral speed difference between a pair of stretching rollers. During the stretching process, the film is heated by the preheating rollers or stretching rollers and stretched longitudinally. In addition, after longitudinal stretching, it is cooled by a cooling roller and sent to the next step. The longitudinally stretched film can then be stretched in the transverse direction using similar preheating and cooling rollers.

[0078] In some embodiments, a stretching plate is used for stretching and cooled by a longitudinal stretching machine. In some embodiments, the longitudinal stretching preheating temperature is about 65°C to about 100°C, about 70°C to about 90°C, or about 74°C to about 85°C, and the quenching temperature is about 20°C to about 70°C, about 25°C to about 65°C, or about 30°C to about 62°C. A transverse traction machine can then be used for orthogonal stretching, heat setting, and cooling. In some embodiments, the orthogonal stretching preheating temperature is in the range of about 75°C to about 125°C, about 80°C to about 110°C, or about 98°C to about 106°C, and the quenching temperature is about 50°C to about 100°C, about 60°C to about 90°C, or about 65°C to about 80°C.

[0079] After the preheat treatment and before the quenching, the unstretched film is biaxially stretched by heat treating the film at a suitable temperature, which may be about 200°C to about 350°C, about 275°C to about 300°C, about 250°C to about 290°C, or about 255°C to about 280°C. In the method of the present technology, the maintenance of the die temperature and the stretch ratio are aspects that affect film formation, crystallinity, and sealability. Therefore, in one aspect, stretching is carried out at a temperature of about 150°C to about 350°C in the machine direction orientation (MDO) or longitudinal direction, including about 200°C to about 325°C, about 225°C to about 300°C, about 250°C to about 290°C, or about 275°C to about 280°C. Stretching is performed at a temperature of about 50°C to 300°C in the cross section or transverse direction orientation (TDO), including about 80°C to about 275°C, about 100°C to about 250°C, about 150°C to about 240°C, or about 215°C to about 230°C. TDO stretching may include a TDO stretching zone and / or a TDO crystallization zone. The TDO stretching zone temperature may be about 50°C to about 250°C, including about 80°C to about 225°C, about 100°C to about 200°C, about 110°C to about 190°C, or about 112°C to about 185°C. The TDO crystallization zone temperature may be about 50°C to about 300°C, including about 100°C to about 280°C, about 175°C to about 275°C, about 200°C to about 250°C, or about 215°C to about 230°C.

[0080] Stretching is carried out in the machine direction orientation (MDO) or longitudinal direction, so that the stretching ratio in the longitudinal direction is about 1 to about 6 times based on the original length of the unstretched film, including about 2 to about 5 times, about 2.5 to about 4 times, about 2.8 to about 3.8 times, about 3 to about 3.6 times, or about 3 to about 3.4 times. Stretching is carried out in the transverse direction orientation (TDO) or cross-sectional direction, so that the stretching ratio is about 1 to about 8 times based on the original width of the unstretched film, including about 1.5 to about 7 times, about 2 to about 6 times, about 2.5 to about 4.8 times, about 3.2 to about 4.5 times, or about 3.5 to about 4.2 times.

[0081] In some embodiments, the first machine direction or longitudinal direction stretch draw ratio may be from about 0.5% to about 4%, including from about 0.8% to about 3%, from about 0.9% to about 2.5%, from about 1% to about 2%, or from about 1.01% to about 1.8%. In some embodiments, the second machine direction or longitudinal direction stretch draw ratio may be from about 1% to about 6%, including from about 2% to about 5%, from about 2.5% to about 4%, from about 2.8% to about 3.8%, or from about 3% to about 3.4%. In some embodiments, the transverse direction or orthogonal direction stretch draw ratio may be from about 1% to about 8%, including from about 1.5% to about 7%, from about 2% to about 6%, from about 2.5% to about 4.5%, or from about 3.5% to about 4.2%.

[0082] Before or after transverse stretching, one or both surfaces of the film may be coated using an online or offline coating process. Online coating may, for example, provide improved adhesion between the metal layer and / or printing ink layer and the film, improved antistatic properties, improved processing properties, or further improved barrier properties of the film. The latter is achieved, for example, by applying a polymer coating material such as polyvinyl alcohol (PVOH), ethylene vinyl alcohol (EVOH), polyvinylidene chloride (PVDC), etc. using an offline coating process. In this case, it is preferred that such a layer be applied to a non-heat-sealable surface, such as the outermost surface of the film, but in some cases the functional layer may be applied to a heat-sealable surface.

[0083] The heat sealing temperature of the biaxially oriented super heat sealable polyester film may be from about 40° C. to about 300° C., including from about 50° C. to about 250° C., from about 100° C. to about 200° C., from about 130° C. to about 180° C., or from about 150° C. to about 160° C. The sealing initiation temperature of the film may be from about 50° C. to about 200° C., including about 60° C., about 80° C., about 100° C., about 110° C., about 120° C., about 130° C., about 140° C., or about 150° C.

[0084] In one aspect, a method for preparing a biaxially oriented super heat sealable polyethylene terephthalate film is provided. The method comprises preparing a core layer mixture comprising polyethylene terephthalate, modified polyethylene terephthalate, post-consumer recycled polyester and a filler, wherein the modified polyethylene terephthalate comprises a fiber-grade polyester; preparing a heat sealable layer mixture comprising a heat sealable copolyester; feeding the core layer mixture into a main extruder to obtain a molten first mixture; feeding the heat sealable layer mixture into a sub-extruder to obtain a molten second mixture; extruding the molten first mixture and the molten second mixture through a die to provide an unstretched film; and and biaxially stretching the unstretched film under preheating conditions and heat treating the film to a temperature of about 250° C. to about 290° C., so that the stretching ratio in the longitudinal direction is about 3 to about 3.6 times based on the original length of the unstretched film, and the stretching ratio in the transverse direction is about 3.2 to about 4.5 times based on the original width of the unstretched film; cooling the stretched film to obtain a biaxially oriented super heat sealable polyethylene terephthalate film; wherein the heat sealing temperature of the biaxially oriented super heat sealable polyethylene terephthalate film is about 100° C. to about 200° C. In some embodiments, the biaxially oriented super heat sealable polyester film of the present technology has at least two layers.

[0085] In some embodiments, the preparation of the heat-sealable layer mixture includes charging terephthalic acid, dimethyl terephthalate or a combination thereof with at least one diol and isophthalic acid into a reactor to obtain a reaction mixture; subjecting the reaction mixture to an esterification reaction at a temperature of about 240° C. to about 270° C. to obtain an esterified prepolymer; charging the esterified prepolymer into a polycondensation reactor and adding one or more polycondensation catalysts selected from silica, antimony compounds and magnesium compounds; subjecting the prepolymer to a polycondensation reaction at a temperature in the range of about 270° C. to about 310° C. to obtain a molten amorphous polymer; cooling and processing the molten polymer to form chips or pellets; and optionally subjecting the obtained chips to solid-state polymerization to obtain a heat-sealable layer mixture comprising a heat-sealable copolyester having an intrinsic viscosity greater than 0.65 dL / g.

[0086] In some embodiments of the methods of the present technology, the heat-sealable copolyester comprises about 35 to about 70 weight percent terephthalic acid, dimethyl terephthalate, or a combination thereof; about 21 weight percent to about 40 weight percent monoethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, hexanediol, cyclohexanedimethanol, or a mixture of any two or more thereof; and about 10 weight percent to about 30 weight percent isophthalic acid. In some embodiments of the methods of the present technology, the core layer mixture comprises about 40 weight percent to about 80 weight percent polyethylene terephthalate polyester; about 0 weight percent to about 30 weight percent fiber-grade polyester; about 20 weight percent to about 100 weight percent post-consumer recycled polyethylene terephthalate; and about 0.05 weight percent to about 0.1 weight percent silica. In some embodiments of the methods of the present technology, the polyethylene terephthalate polyester of the core layer mixture comprises about 70 wt % to about 85 wt % terephthalic acid, about 20 wt % to about 30 wt % monoethylene glycol, and about 0.5 wt % to about 5 wt % diethylene glycol. In some embodiments of the methods of the present technology, the fiber-grade polyester of the core layer mixture comprises about 65 wt % to about 85 wt % terephthalic acid, about 20 wt % to about 30 wt % monoethylene glycol, and about 2 wt % to about 10 wt % diethylene glycol.

[0087] In some embodiments of the methods of the present technology, the processing step includes one or more steps of preheating, stretching, and cooling the extruded structure. In some embodiments, stretching is performed sequentially or simultaneously in the machine direction and the transverse direction. In some embodiments, preheating, stretching, and cooling include machine direction preheating, stretching, and cooling, followed by transverse direction preheating, stretching, and cooling. In some embodiments, the preheating conditions include passing the unstretched film through a machine direction preheating zone at a temperature of about 70°C to about 90°C, stretching the preheated structure in the longitudinal direction, and passing the longitudinally stretched film through a machine direction cooling zone at a temperature of about 70°C to about 90°C.

[0088] In some embodiments of the method of the present technology, the method also includes passing the cooled longitudinally stretched film through a transverse direction preheating zone having a temperature of about 92°C to about 110°C, stretching the preheated film along the transverse direction, and passing the transversely stretched film through a machine direction cooling zone having a temperature of about 60°C to about 85°C.

[0089] In some embodiments, the method of the present technology further comprises adding an additional layer to the biaxially oriented super heat sealable polyester film. In some embodiments, the additional layer comprises one or more of a sealant layer, a print layer, a metal layer, a barrier layer, an adhesive layer, a coating, a primer layer, and a protective layer.

[0090] In some embodiments, the PET polymer and modified PET polymer in the core layer can be replaced by up to and including 100% recycled PET. However, it is preferred that the sealant layer component is not replaced by recycled PET. This is because its high comonomer content prevents it from crystallizing during stretching and at elevated temperatures, thereby providing sealing strength to the film. The overall ratio of the core layer to the sealant layer may be about 50:50, including but not limited to about 60:40. Increasing the PET polymer, modified PET polymer, and recycled PET content will result in lower seal strength because the comonomer content in the sealant layer is responsible for imparting super sealability to the film. However, the PET polymer, modified PET polymer, and recycled PET (R pet) content will provide mechanical strength and stability at higher temperatures.

[0091] The biaxially oriented super heat sealable polyester film can be used alone or as a laminate. The film may optionally include other layers, including but not limited to a sealant layer, a printing layer, a metal layer, a barrier layer, an adhesive layer, a coating, a primer layer, a protective layer or any combination of two or more thereof. The film can be used to produce a high barrier film or laminate structure with a functional coating and metal deposition on the film surface, including, for example, a sealable transparent film, a metallized sealable film (for example, a surface metallized sealable film with better printability on a metal surface, a metal surface coated with a primer for ink and adhesive adhesion), a laminate structure including a sealable film. In particular, the present technology provides a biaxially oriented PET film and a laminate structure that can provide ultrahigh heat seal strength, and includes a method for producing and using the sealable film and laminate structure.

[0092] The biaxially oriented super heat sealable polyester film can be used to make a multilayer high barrier film (laminate). The multilayer high barrier film including the biaxially oriented super heat sealable polyester film of the present technology may include a barrier layer disposed on at least one of the one or more core layers. The barrier layer may include at least one of ethylene vinyl alcohol copolymer, polyvinyl alcohol polymer and copolymer, or polyvinylidene chloride, aluminum, silicon oxide and aluminum oxide. The barrier film may be unprinted or reverse printed. The multilayer high barrier film may have a thickness of 0.30 to 0.40 g / m 2 - Water vapor transmission rate in the range of 0.40 to 0.50 cc / m 2 - Day-range oxygen transfer rates.

[0093] The films and polymer compositions described herein can be used in various applications. The films can be used in vertical form filling seal (VFFS) and horizontal form filling seal (HFFS), wherein VFFS is a more preferred technology. The films have excellent runability in the bag making process. Typical end-use applications include, but are not limited to, packaging, insulating materials, print media, electronics applications, acoustic applications, and food contact applications. The films can be used as recyclable flexible packaging solutions, such as bags and laminates for food, medical and cosmetic packaging. For example, the films can be used for packaging food and other consumer products, medicines, powder packaging bags, tea powder packaging, spice packaging bags, outer packaging bags, vacuum packaging, etc. The films are suitable for use as barrier films, release films, or as packaging materials. The films are particularly suitable for packaging food, medical products, and other consumer products that require high resistance to bag breakage in a tray, wherein a peelable polyester film is used to open the package. The films can also be used to manufacture a single material multilayer laminate to obtain a high packaging strength with improved barrier properties. In one aspect, a packaging material is provided, which includes a biaxially oriented super heat sealable polyester film of the present technology. In yet another aspect, a packaging material is provided, comprising a biaxially oriented super heat sealable polyester film produced by the method of the present technology. In some embodiments, the film comprises a food grade packaging film or a medical product packaging film.

[0094] Compositions, films and methods described herein provide significant advantages, including but not limited to greatly reducing the complexity of packaging products, reducing fluctuations in the quality and quantity of recycled products delivered to consumers, and reducing the amount of non-recyclable fractions due to the ability to replace multilayer laminates with single-layer or multilayer single-material laminates. The use of modified PET polymers and PCR-grade PET content will provide mechanical strength and stability at higher temperatures. The films are cost-effective, environmentally friendly, and reduce carbon footprints because they are produced with PCR-grade polyethylene terephthalate. The packaging made of these films is also recyclable. In addition, the films have excellent resistance to bag breakage, better oxygen and moisture barrier properties, high mechanical strength (e.g., tensile strength, toughness and elongation), improved optical properties, balanced shrinkage in the longitudinal and machine directions at elevated temperatures, high temperature dimensional stability, puncture resistance, high seal strength and low seal initiation temperature, produce single-material films or laminate packaging with high seal strength, and can replace cast PE films, blown PE and / or CPP films to provide sustainable packaging solutions.

[0095] The invention thus generally described will be more readily understood by reference to the following embodiments, which are provided by way of illustration and are not intended to be limiting of the invention.

[0096] Example

[0097] In the following examples and throughout the application, the following abbreviations have the following meanings. If not defined, the terms have their generally accepted meanings.

[0098] PET: Polyethylene terephthalate,

[0099] DMT: dimethyl terephthalate,

[0100] IPA: Isophthalic acid,

[0101] NPG: 2,2-dimethylpropane-1,3-diol,

[0102] CHDM: cyclohexanedimethanol,

[0103] BHET: Bis(2-hydroxyethyl)terephthalate,

[0104] PTA: Purified terephthalic acid,

[0105] rPET: recycled PET,

[0106] PCR: post-consumer recycled,

[0107] MEG / EG: Monoethylene glycol / ethylene glycol,

[0108] DEG: diethylene glycol,

[0109] BOPET: Biaxially oriented polyester,

[0110] APET: Amorphous polyethylene terephthalate,

[0111] CPET: Crystalline polyethylene terephthalate,

[0112] SSP: Solid State Polymerization,

[0113] dl / gm: deciliter / gram,

[0114] wt.%: weight percentage,

[0115] IV: intrinsic viscosity,

[0116] T g : Glass transition temperature,

[0117] T ch : Crystallization temperature,

[0118] T m : Melting temperature

[0119] Intrinsic viscosity

[0120] The intrinsic viscosity (IV) is a measure of the molecular weight of a polymer and is measured from a dilute solution using an Ubbelohde viscometer. All intrinsic viscosities were measured in a 60:40 mixture of phenol and s-tetrachloroethane at a concentration of 0.5%. The flow times of the solvents and solutions were checked in an IV water bath maintained at 25°C. IV, η, was obtained from the relative viscosity measurements ηr of a single polymer concentration by using the Billmeyer equation:

[0121] IV=[η]=0.25[(RV-1)+3ln RV] / c

[0122] Where: η is the intrinsic viscosity, RV is the relative viscosity; c is the concentration of the polymer solution (unit: g / dL). The relative viscosity (RV) is derived from the ratio between the flow time of the solution (t) and the flow time of the pure solvent mixture (t0).

[0123] RV=n rel = Flow time of solution (t) / Flow time of solvent (t0)

[0124] IV must be controlled to keep the processability and final properties of the polymer within the desired range. For greater accuracy, use a Class "A" certified pipette for IV measurements.

[0125] DSC analysis

[0126] Differential scanning calorimetry is a thermal analyzer that can accurately and quickly determine the thermal behavior of polymers, such as the glass transition temperature (Tg), crystallization exotherm peak temperature (Tch), endotherm peak temperature (Tm), crystallization heat (ΔH), and melting heat of all materials. A Perkin-Elmer model Jade DSC was used to monitor the thermal properties of all polymer samples, with a heating and cooling rate of 10°C per minute. A nitrogen purge was used to prevent oxidative degradation.

[0127] Crystallinity analysis by DSC and DGC

[0128] Differential scanning calorimetry (DSC) and density gradient column (DGC) were used to calculate the crystallinity of the polymer samples.

[0129] The crystallinity was calculated by DSC using the heat of fusion (ΔH) at Tm1 (heat 1 cycle) and the specific heat of the polymer.

[0130] The crystallinity was calculated by DGC (density gradient column) with the aid of known standard spheres floating on a Lloyds densitometer.

[0131] The following examples are given to illustrate various embodiments of the present invention and are not intended to limit the present invention in any way. The examples of the present invention and the methods described herein currently represent preferred embodiments and are exemplary and are not intended to be used as limitations on the scope of the present invention. Those skilled in the art will appreciate variations and other uses thereof, which are encompassed within the spirit of the present invention as defined by the scope of the claims.

[0132] Example 1: Preparation of heat-sealable copolyester 1. A 0.2 m 3 30 kg ethylene glycol, 56.3 kg PTA and 12.8 kg IPA are added to a reactor of 1.5 liter volume. Esterification is carried out for 2 to 3 hours at a temperature of 248 to 260° C. and a pressure of up to 3.0 bar. After about 90% of the esterification is completed, the reactor is decompressed and trimethyl phosphate is added. The resulting BHET (bis(hydroxyethyl) terephthalate) is then transferred to a polycondensation reactor. 34.8 g antimony trioxide, 52 g MgAc2 and 400 g SiO2 slurry (10% concentrate in MEG) are added and the reaction mixture is kept for 10 minutes for mixing. The polycondensation reaction is then carried out at a temperature of 280° C. to 300° C. at a pressure of less than 0.2 torr. After reaching sufficient melt viscosity (e.g., about 1036 poise at 280° C.), the polymerization is stopped. The molten polymer is cooled in cold water and then chopped to form pellets. The intrinsic viscosity of the amorphous polymer was 0.680 dl / g and the product yield from the reactor was greater than 98.5% (yield).

[0133] Example 2: Preparation of heat-sealable copolyester 2 A 0.2 m 3 30 kg ethylene glycol, 51.1 kg PTA and 18 kg IPA were added to a reactor of 1.5 wt % volume. Esterification was carried out for 2 to 3 hours at a temperature of 248° C. to 260° C. and a pressure of up to 3.0 bar. After about 90% of the esterification was completed, the reactor was decompressed and trimethyl phosphate was added. BHET was transferred to a polycondensation reactor. 34.8 g antimony trioxide, 52 g MgAc2 and 400 g SiO2 slurry (10% concentrate in MEG) were added and the reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280° C. to 300° C. at a pressure of less than 0.2 Torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form pellets. The intrinsic viscosity of the amorphous polymer was 0.680 dl / g, and the product yield from the reactor was greater than 98.5% (yield).

[0134] Example 3: Preparation of heat-sealable copolyester 3. A 0.2 m 3 30 kg ethylene glycol, 44.7 kg PTA and 24.0 kg IPA were added to a reactor of 1.5 wt % volume. Esterification was carried out for 2-3 hours at a temperature of 248-260° C. and a pressure of up to 3.0 bar. After 90% of the esterification was completed, the reactor was depressurized and trimethyl phosphate was added. BHET was transferred to a polycondensation reactor. 34.8 g antimony trioxide, 52 g MgAc2 and 400 g SiO2 slurry (10% concentrate in MEG) were added and the reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280° C. to 300° C. at a pressure of less than 0.2 torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form pellets. The intrinsic viscosity of the amorphous polymer was 0.680 dl / g and the product yield from the reactor was greater than 98.1% (yield).

[0135] Due to the high comonomer content, the polymer cannot be crystallized and cannot be dried to the minimum moisture level, which causes the intrinsic viscosity to drop significantly during processing. Therefore, the intrinsic viscosity is in the melt phase in the three reactor process (esterification, prepolymerization and polymerization) and a blending process of up to 30% is used.

[0136] Example 4: Preparation of heat-sealable copolyester 4. A 0.2 m 3 A reactor of 1.5 liter volume was charged with 28 kg ethylene glycol, 3.6 kg neopentyl glycol, 48.2 kg PTA and 20 kg IPA. Esterification was carried out for 2-3 hours at a temperature of 248-260° C. and a pressure of up to 3.0 bar. After 90% of the esterification was completed, the reactor was depressurized and trimethyl phosphate was added. BHET was transferred to a polycondensation reactor. 34.8 g antimony trioxide, 52 g MgAc2 and 400 g SiO2 slurry (10% concentrate in MEG) were added and the reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280° C. to 300° C. at a pressure of less than 0.2 torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form pellets. The intrinsic viscosity of the amorphous polymer was 0.680 dl / g, and the product yield from the reactor was greater than 98.5% (yield).

[0137] Due to the high comonomer content, the polymer cannot be crystallized and cannot be dried to the minimum moisture level, which causes the intrinsic viscosity to drop significantly during processing. Therefore, the intrinsic viscosity increases in the melt phase in the three reactor processes (esterification, prepolymerization and polymerization).

[0138] Example 5: Preparation of heat-sealable copolyester 5. A 8.0 m3 / s reactor equipped with a mechanical stirrer, a packed reflux tower, a nitrogen inlet and a heat source was added. 3 A reactor of 1.5 wt % was charged with 495.0 kg ethylene glycol, 259.2 kg neopentyl glycol and 1490.6 kg PTA. Esterification was carried out for 2-3 hours at a temperature of 248-260° C. and a pressure of up to 3.0 bar. After 90% of the esterification was completed, the reactor was decompressed and trimethyl phosphate was added. BHET was transferred to a polycondensation reactor. 435 ppm of antimony trioxide, 650 ppm of MgAc2 and 300 ppm of SiO2 slurry (10% concentrate in MEG) were added and the reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280° C. to 300° C. at a pressure of less than 0.2 torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form pellets. The intrinsic viscosity of the amorphous polymer was 0.745 dl / g, and the product yield from the reactor was greater than 98.5% (yield).

[0139] For some copolyesters, the polymer cannot be crystallized in a drum dryer due to the high comonomer content. In such cases, a three-stage crystallization is performed. The material depicted in Table 1 Example 5NH1 is passed through a rotary crystallizer at 60% throughput and a temperature of 80°C to 90°C, the material is transferred through a fluidized bed crystallizer with a product temperature as high as 100°C to 110°C, and finally the material is charged into a drum dryer and heated to a product temperature of 70°C to 160°C for 8 to 12 hours. The final polymer has a crystallinity of 23% and a moisture of 100 ppm, and the material can be easily dried before processing.

[0140] Example 6: Preparation of heat sealable copolyester 6. A copolyester was prepared using a 70:30 ratio blend from Example 3 and Example 5. The intrinsic viscosity of the amorphous polymer was 0.745 dl / g and the seal strength of the film was 1450 gm / inch.

[0141] Table 1 lists the raw materials used to synthesize the copolyesters of Examples 1 to 6.

[0142] Table 1: Formulations used to prepare low melting point copolyesters. Table 1: Formulations used to prepare low melting point copolyesters.

[0143]

[0144]

[0145] The DSC parameters used to measure various properties of the polymer, including intrinsic viscosity (IV), seal strength, melting point, and glass transition temperature, are provided in Table 2, and the results of the DSC analysis are summarized in Table 3 below.

[0146] Table 2: DSC parameters used for analysis

[0147] Example No. 1 2 3 4 5 6 Final cutoff value 5.7 amp. 5.2amp. 5.5amp. 5.7 amp. 42.5amp - EI cycle time (min) 270min 245min 250min 235min 296min - EI peak temperature (℃) 261.5 258.7 258.0 258.1 260.0 - PC cycle time (min) 153min 148min 168min 149min 229min - PC peak temperature (℃) 284.1 286.3 284.5 284.4 288.3 -

[0148] Table 3: Analysis of the prepared copolyesters

[0149]

[0150]

[0151] Example 7: Solid State Polymerization

[0152] BRT Polymer: The molecular weight of the polymers of Examples 1-6 can be significantly increased by first loading the polymer pellets onto a drum dryer and heating the contents to up to 110°C for 11 hours under a nitrogen stream to obtain crystallized polymer. After crystallization, a high vacuum was applied to the dryer and the crystallized pellets were heated up to 230°C for 10 to 15 hours. This achieved solid state polymerization and allowed for a significant increase in molecular weight. Typically, the film manufacturing process uses 0.620 dl / gm PET IV. However, in this process, 0.750 dl / gm high IV PET was used for smooth operation and higher seal strength.

[0153] Example 8: Preparation of FGT PET chips

[0154] A 8.0 m3 / s reactor equipped with a mechanical stirrer, a packed reflux tower, a nitrogen inlet and a heat source was added. 3 A reactor of 1.5 liter volume was charged with 616.23 kg ethylene glycol, 105 kg diethylene glycol and 1601.18 kg PTA. Esterification was carried out for 2-3 hours at a temperature of 248-260° C. and a pressure of up to 3.0 bar. After 90% of the esterification was completed, the reactor was decompressed and trimethyl phosphate was added. BHET was transferred to a polycondensation reactor. 435 ppm of antimony trioxide, 150 ppm of MgAc2 were added and the reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280° C. to 300° C. at a pressure of less than 0.2 torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form pellets. The intrinsic viscosity of the amorphous polymer was 0.650 dl / g, and the product yield from the reactor was greater than 99.1% (yield).

[0155] During the manufacturing process, crystallization of the polymer is carried out using a crystallizer to induce controlled crystallinity in the molten PET (crystallinity 40-50%). This controlled crystallization will promote the formation of a structured crystalline matrix within the polymer. The result is enhanced mechanical strength, dimensional stability and barrier properties of the film (temperature 160-170°C). After the crystallization process, the PET chips are dried in a dryer to eliminate residual moisture. The dryer uses hot air to efficiently evaporate the water content, ensuring that the finished product reaches the desired moisture level. The drying temperature is in the range of 165-170°C, and the moisture is reduced from 2000ppm to 40-60ppm. This step is critical to achieving uniform film quality, physical properties and optical clarity.

[0156] The dried PET chips are introduced into a vacuum hopper, which will facilitate controlled feeding and metering of the PET resin into the extruder. Applying a vacuum to the hopper will ensure a consistent and uniform flow of the polymer material, thereby providing consistent film thickness and properties.

[0157] Example 9: Method for producing a biaxially oriented super heat sealable polyester film.

[0158] A. General Methods for Extruding Biaxially Oriented Films

[0159] (a) feeding thermoplastic polyethylene terephthalate (PET), modified PET pellets and post-consumer recycled polyester chips in combination with silica (filler) having desired properties into a main extrusion line at a temperature in the range of 255-280° C. to obtain a first mixture; and

[0160] (b) The copolyesters of Examples 1-6 presented in Table 1 were fed into a sub-extrusion process at a temperature of 260-280° C. to obtain a second mixture.

[0161] Steps (a) and (b) of the extrusion process allow the materials to melt separately, and then the molten first mixture polymer passes through a filter. The first mixture of step (a) and the second mixture of step (b) are then laminated together in a feed block to produce a laminated molten structure and extruded through a die to shape, form or extrude the BOPET material into a desired configuration.

[0162] B. Preparation of Biaxially Oriented Films

[0163] A biaxially oriented super heat sealable polyester film with a two-layer structure having different thicknesses (such as 15μ, 30μ or 50μ) was prepared using different core compositions and the copolyesters of Examples 1-6. A biaxially oriented super heat sealable polyester film was prepared via a conventional sequential biaxial orientation machine with a main line extrusion and a sub-extrusion process. A stretching plate was used for stretching and a longitudinal stretching machine was used for cooling, wherein the longitudinal stretching ratio was 3.0 to 3.4 times, the longitudinal stretching preheating temperature was 74°C to 85°C, and the quenching temperature was 30°C to 62°C. A transverse traction machine was then used for orthogonal stretching, heat setting and cooling. The orthogonal stretching ratio was 3.5 to 4.2 times, the orthogonal stretching preheating temperature was 98°C to 106°C, and the quenching temperature was 65°C to 80°C.

[0164] Preparation of membrane A

[0165] Table 4: Outer layer of film A

[0166]

[0167] Film A is a biaxially oriented super heat sealable PET film having a two-layer structure, i.e., inner layer (heat sealable / sealant layer) / outer layer (core layer). The composition of Examples 1-6 is used as the inner layer. The outer layer is made of polyethylene terephthalate (PET), post-consumer recycled (PCR) grade polyethylene terephthalate chips and silica as a filler, and its composition is shown in Table 4. The outer layer and / or structural layer of the film comprises: 78% PET, which is composed of 73.5 purified terephthalic acid (PTA) + 25% ethylene glycol (EG) + 1.5% diethylene glycol (DEG); 22% PCR grade chips (Starlinger iV+ technology approved by EFSA); and 0.075% (750ppm) silica as a filler. Various biaxially oriented super high heat sealable polyester films (Films A1-A6) having a two-layer structure and a thickness of 20μ were produced using a series of processing parameters listed in Table 5 below.

[0168]

[0169]

[0170] Various other films were similarly prepared using the process and parameters disclosed in Table 5. The compositions of Examples 1-6 were used as the inner layer, while the outer layer compositions varied as listed in Examples BD below. The compositions used to prepare the biaxially oriented super heat sealable polyester films of Examples B, C and D are disclosed below.

[0171] Preparation of membrane B

[0172] Table 6: Outer Layer of Film B

[0173]

[0174] Film B is a biaxially oriented super heat sealable PET film, wherein the core layer comprises thermoplastic polyethylene terephthalate, modified polyethylene terephthalate, PCR grade polyethylene terephthalate flakes and silica as a filler. The outer layer and / or structural layer of the film comprises: 58% PET, which is composed of 73.5 purified terephthalic acid (PTA) + 25% ethylene glycol (EG) + 1.5% diethylene glycol (DEG); 20% modified polyethylene terephthalate; 22% PCR grade flakes; and 0.075% (750 ppm) silica as a filler. The composition of Examples 1-6 is used as the inner layer.

[0175] Preparation of membrane C

[0176] Table 7: Outer Layer of Film C

[0177]

[0178] Film C is a biaxially oriented super heat sealable PET film, wherein the core layer comprises thermoplastic polyethylene terephthalate, PCR grade polyethylene terephthalate flakes, copolyester flakes and silica as a filler. The outer layer and / or structural layer of the film comprises 55% PET, which is composed of 73.5 purified terephthalic acid (PTA) + 25% ethylene glycol (EG) + 1.5% diethylene glycol (DEG); and 45% PCR grade flakes; and 0.075% (750 ppm) silica as a filler. The composition of Examples 1-6 is used as an inner layer.

[0179] Preparation of membrane D

[0180] Table 8: Outer layer of film D

[0181]

[0182] Film D is a biaxially oriented super heat sealable PET film, wherein the core layer comprises post-consumer recycled (PCR) grade polyethylene terephthalate flakes and silica as a filler. The outer and / or structural layers of the film comprise: 100% PCR grade flakes and 0.075% (750 ppm) silica as a filler. The compositions of Examples 1-6 are used as the inner layer.

[0183] C. Analysis of Biaxially Oriented Films

[0184] The prepared films were analyzed for tensile strength, elongation, sealing, shrinkage and barrier properties. Analysis results of film A composition

[0185] Table 9: Properties of 20μ Film A

[0186]

[0187]

[0188] The films prepared using the copolymer compositions of Examples 4 and 6 exhibited enhanced sealability. The copolymer compositions demonstrated in Examples 4 and 6 provided superior sealability compared to Copolymer Examples 1, 2, 3, and 5. Similar analyses can be performed on the film compositions of Examples B, C, and D.

[0189] Example 10: Comparative Example

[0190] Biaxially oriented super high heat sealable polyester films having a two-layer structure and comparative two-layer biaxially oriented standard (TF balanced shrink) polyester films, both having different thicknesses (such as 15μ, 30μ or 50μ), were produced using the processing parameters listed in Table 10 below.

[0191] Table 9 shows that the films of Example A were made from six different copolyester compositions, resulting in A1, A2, A3, A4, A5, and A6. Among all the Film A Examples, A4 and A6 showed better seal strength, with A6 being the best among A1 to A6.

[0192] Table 10 serves as an example to illustrate the differences between heat sealable films (15, 30, 50 microns) and non-heat sealable films (5, 30, 50 micron standard films). Example E of a 15 micron sealable film, Example F of a 30 micron sealable film, and Example G of a 50 micron sealable film were compared with non-sealable 15, 30, and 50 micron standard films in terms of processing parameters and seal strength.

[0193]

[0194]

[0195]

[0196]

[0197] Example 11: Method of Preparing Laminated Compositions

[0198] The first mixture from step (a) and the second mixture from step (b) were laminated together in a feedblock to produce a laminated molten structure in an extrusion die as described in Example 9 using the main extrusion and coextrusion temperatures described in Tables 5 and 10. This process produced a two-layer structure comprising a core layer and a copolyester layer.

[0199] Example 12: Method of Preparing a Packaging Composition

[0200] (I) Application of super heat sealable film as single layer packaging

[0201] a. Surface printing film

[0202] like Figure 2 As shown in the drawings, the films described in the above embodiments can be modified using conventional printing methods to include a surface printing layer on top of the sealant layer described in Examples 1-6 to improve aesthetics and brand reputation. These environmentally friendly, recyclable films are designed to produce bags or outer wrap packaging to ensure product protection. These films can produce single-layer packaging bags that use less plastic, thereby reducing plastic waste while still providing convenient sealing options. The benefit of such packaging is that due to the inherent sealing properties of the film, no sealant layer laminate is required. For surface printed films, the water vapor transmission rate (WVTR) is less than 40gm / m 2 / day, oxygen transmission rate (OTR) less than 100cc / m 2 / sky.

[0203] b. Surface metallized films for high barrier applications

[0204] like Figure 3 As shown in , the films described in the above embodiments can be modified to include a surface metallization layer above the sealant layer described in Examples 1-6. Film metallization refers to the process of depositing a thin layer of metal on the outer surface of the film of the present technology. These recyclable films are specifically designed to produce bags or overwrap packaging with high barrier properties to oxygen and moisture, thereby ensuring optimal product protection. In cases where the metal is in direct contact with the environment, a metal protective coating is required to prevent any potential reaction or oxidation of the metal. The metal layer is typically applied using standard methods, such as vacuum metallization or sputtering. The process produces an ultra-high barrier film or laminate with a water vapor transmission rate (WVTR) of less than 0.30 gm / m 2 / day, oxygen transmission rate (OTR) less than 0.40cc / m 2 / sky.

[0205] (II) Ultra-high sealant films for use in multi-layer mono-material laminates for packaging

[0206] Multi-layer mono-material sustainable laminates offer a sustainable packaging solution that combines the benefits of recyclability, barrier properties, strength and versatility and are often used in modified atmosphere packaging (MAP).

[0207] c. Transparent film laminate

[0208] like Figure 4As shown in the figure, the films described in the above embodiments can be modified to include reverse printed or unprinted films. Transparent single material multi-layer sustainable laminates are innovative packaging materials that have transparency, sustainability and multiple layers to improve performance. These laminates are designed to provide clear and transparent packaging solutions while minimizing the impact on the environment. The transparent film laminate is made using two different polyester films. One is the EUHSCO film of the present technology (ester super heat seal inward, corona treated outer film), and the other is a non-sealable ordinary, corona treated, chemical primer and / or reverse printed film. The non-sealable film is laminated with EUHSCO using extrusion lamination, solvent-based lamination process or solvent-free lamination process. This type of laminate is produced by using a reverse printed or unprinted film, which is then laminated with a sealable film using a compatible adhesive. The water vapor transmission rate (WVTR) of the transparent film laminate is less than 40gm / m 2 / day, oxygen transmission rate (OTR) less than 100cc / m 2 / sky.

[0209] d. High barrier laminate

[0210] like Figure 5 As shown in the figure, the films described in the above embodiments can be modified to include a high barrier layer. High barrier laminates are produced by using a reverse printed or unprinted barrier layer coated film (coating material such as PVDC, EVOH or PVOH). The film is then laminated with a sealable film using a compatible adhesive. High barrier laminates are manufactured using extrusion lamination, solvent-based lamination processes or solvent-free lamination processes. High barrier laminates are specifically designed to provide clear and transparent packaging solutions while providing excellent resistance to oxygen, moisture and aroma. The water vapor transmission rate (WVTR) of the high barrier film is less than 8gm / m 2 / day, oxygen transmission rate (OTR) less than 8cc / m 2 / sky.

[0211] e. Ultra-high barrier laminate

[0212] like Figure 6As shown in the diagram, the films described in the above embodiments can be modified to include an ultra-high barrier layer. Ultra-high barrier multi-layer single material laminates provide a combination of advanced barrier properties, visual aesthetics and sustainability. These laminates are also used as a substitute for aluminum foil-based laminates, which are traditionally used to provide barriers in modified atmosphere packaging (MAP). The ultra-high barrier laminates are made using two different polyester films. One is a EUHSCOM film metallized on the non-sealable side, and the other is a non-sealable corona or chemical primer and / or reverse printed film. They are laminated together with EUHSCO using extrusion lamination, a solvent-based lamination process or a solvent-free lamination process. The water vapor transmission rate (WVTR) of the ultra-high barrier film is less than 0.20gm / m 2 / day, oxygen transmission rate (OTR) less than 0.20cc / m 2 / sky.

[0213] The invention thus generally described will be more readily understood by reference to the following embodiments, which are provided by way of illustration and are not intended to be limiting of the invention.

[0214] While certain embodiments have been illustrated and described, it will be appreciated that changes and modifications may be made thereto in accordance with ordinary skill in the art without departing from the technology in its broader aspects as defined in the following claims.

[0215] The embodiments schematically described herein may be appropriately implemented in the absence of any one or more elements, one or more limitations not specifically disclosed herein. Therefore, for example, the terms "comprise", "include", "contain", etc. should be widely understood without limitation. In addition, the terms and expressions adopted herein have been used as descriptive and non-restrictive terms, and when using such terms and expressions, it is not intended to exclude any equivalents of the features shown and described or parts thereof, but it should be recognized that various modifications can be made within the scope of the claimed technology. In addition, the phrase "essentially consisting of..." will be understood to include those elements specifically described and those other elements that will not substantially affect the basic and novel features of the claimed technology. The phrase "consisting of..." excludes any unspecified elements.

[0216] The present disclosure is not limited to the specific embodiments described in this application. Many modifications and variations can be made without departing from its spirit and scope, as will be apparent to those skilled in the art. In addition to those listed herein, functionally equivalent methods and compositions within the scope of the present disclosure will be apparent to those skilled in the art based on the foregoing description. Such modifications and variations are intended to fall within the scope of the appended claims. The present disclosure will be limited only by the terms of the appended claims and the full scope of equivalents enjoyed by such claims. It should be understood that the present disclosure is not limited to specific methods, reagents, compounds, compositions or biological systems, which may of course vary. It should also be understood that the terms used herein are only for the purpose of describing specific embodiments and not for limiting purposes.

[0217] In addition, where features or aspects of the disclosure are described in terms of Markush groups, those skilled in the art will recognize that the disclosure is also thereby described in terms of any individual member or subgroup of members of the Markush group.

[0218] As will be understood by those skilled in the art, for any and all purposes, particularly with respect to providing a written description, all ranges disclosed herein also encompass any and all possible subranges or combinations of any two or more subranges thereof. Any listed range can be easily identified as fully describing and allowing the same range to be decomposed into at least equal halves, thirds, quarters, fifths, tenths, etc. As non-limiting examples, each range discussed herein can be easily decomposed into lower thirds, middle thirds, and upper thirds, etc. As will be understood by those skilled in the art, all languages ​​such as "at most," "at least," "greater than," "less than," etc. include the cited numbers and refer to the ranges that can be subsequently decomposed into subranges as described above. Finally, as will be understood by those skilled in the art, ranges include each individual member.

[0219] All publications, patent applications, issued patents, and other documents mentioned in this specification are incorporated herein by reference to the same extent as if each individual publication, patent application, issued patent, or other document was specifically and individually indicated to be incorporated herein by reference in its entirety. Definitions contained in the text incorporated by reference shall not be construed to the extent they conflict with definitions in this disclosure.

[0220] Further embodiments are set forth in the accompanying claims.

Claims

1. A biaxially oriented super heat sealable polyester film, the film comprising: a core layer comprising polyethylene terephthalate, post-consumer recycled grade polyethylene terephthalate, and a filler; and a heat-sealable layer disposed on at least one surface of the core layer and comprising a copolyester composition; in: The copolyester composition of the heat-sealable layer comprises: Terephthalic acid, dimethyl terephthalate or a combination thereof; at least one diol selected from the group consisting of monoethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, hexanediol, and cyclohexanedimethanol; and Isophthalic acid; The biaxially oriented super heat sealable polyester film is 2 The seal strength is greater than 800 gmf / inch when the pressure seal is sealed for 1 second.

2. The biaxially oriented super heat sealable polyester film according to claim 1, wherein the film has at least two layers.

3. The biaxially oriented super heat sealable polyester film according to claim 1 or claim 2, wherein the heat sealable copolyester comprises: (a) 35 to 75 weight percent of terephthalic acid, dimethyl terephthalate, or a combination thereof; (b) 25 to 40% by weight of at least one diol selected from monoethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, hexanediol and cyclohexanedimethanol; and (c) 10 to 30% by weight of isophthalic acid.

4. The biaxially oriented super heat sealable polyester film according to any one of claims 1 to 3, wherein the core layer mixture comprises: (i) 40 to 80% by weight of polyethylene terephthalate polyester; (ii) 0 to 30 wt. % of a modified polyethylene terephthalate polyester which is a fiber grade polyester; (iii) 20 to 100 weight percent post-consumer recycled polyethylene terephthalate; and (iv) 0.05 to 0.1 wt. % of silica.

5. The biaxially oriented super heat sealable polyester film according to claim 4, wherein the polyethylene terephthalate polyester in the core layer mixture comprises 70 to 80 wt% terephthalic acid, 22 to 30 wt% monoethylene glycol and 0.5 to 5 wt% diethylene glycol.

6. The biaxially oriented super heat sealable polyester film according to claim 4, wherein the fiber grade polyester in the core layer mixture comprises 68 to 85 wt% of terephthalic acid, 20 to 30 wt% of monoethylene glycol and 2 to 10 wt% of diethylene glycol.

7. The biaxially oriented super heat sealable polyester film according to any one of claims 1 to 6, having a total thickness of 15 to 50 μm, wherein the core layer accounts for 50% to 80% of the total thickness of the film.

8. The biaxially oriented super heat sealable polyester film according to any one of claims 1 to 7, wherein the film has one or more of the following: When the temperature is 140℃ and the pressure is 4kg / cm 2 The seal strength of the pressure seal at 1 second is 800gmf / inch to 4500gmf / inch; A total thickness of 15 μm to 50 μm, wherein the core layer accounts for about 50% to about 80% of the total thickness of the film; The shrinkage rate measured according to ASTM D1204 after treatment with hot air at 150° C. for 30 minutes is about 2% or less in each of the longitudinal and width directions; A puncture resistance of about 5.5 N or greater as measured according to ASTM F1306; Tensile strength at break measured according to ASTM D882 is 1300kg / cm 2 Up to 1900kg / cm 2 ;as well as Elongation at break measured according to ASTM D882 is 100kg / cm 2 Up to 160kg / cm 2 .

9. The biaxially oriented super heat sealable polyester film according to claim 1, wherein the film has a g / m 2 - Water vapor transmission rate in the range of 0.40 to 100 cc / m 2 - Day-range oxygen transfer rates.

10. The biaxially oriented super heat sealable polyester film according to any one of claims 1 to 9, further comprising one or more of a sealant layer, a print layer, a metal layer, a barrier layer, an adhesive layer, a coating layer, a primer layer and a protective layer.

11. A multilayer high barrier film, comprising the biaxially oriented super heat sealable polyester film according to any one of claims 1 to 10, with a barrier layer disposed on at least one of the one or more core layers; wherein the barrier layer comprises at least one of ethylene vinyl alcohol copolymers, polyvinyl alcohol polymers and copolymers, or polyvinylidene chloride, aluminum, silicon oxide and aluminum oxide; and wherein the film is unprinted or reverse printed.

12. The multi-layer high barrier film according to claim 11, wherein the film has a g / m 2 - Water vapor transmission rate in the range of 0.20 to 0.50 cc / m 2 - Day-range oxygen transfer rates.

13. A copolyester composition, comprising: a first polymer composition comprising purified terephthalic acid, ethylene glycol, and isophthalic acid; and a second polymer composition comprising purified terephthalic acid, ethylene glycol, and neopentyl glycol; The weight ratio of the first polymer composition to the second polymer composition is in the range of 70:

30.

14. A method for preparing a biaxially oriented super heat sealable polyethylene terephthalate film, the method comprising: preparing a core layer mixture comprising polyethylene terephthalate, modified polyethylene terephthalate, post-consumer recycled polyester, and a filler, wherein the modified polyethylene terephthalate comprises a fiber-grade polyester; preparing a heat sealable layer mixture comprising a heat sealable copolyester; feeding the core layer mixture into a main extruder to obtain a molten first mixture; feeding the heat sealable layer mixture into a sub-extruder to obtain a molten second mixture; extruding the molten first mixture and the molten second mixture through a die to provide an unstretched film; as well as biaxially stretching the unstretched film under preheating conditions and heat treating the film to a temperature of 250° C. to 290° C. such that a stretching ratio in a longitudinal direction is 3 to 3.6 times based on an original length of the unstretched film, and a stretching ratio in a transverse direction is 3.2 to 4.5 times based on an original width of the unstretched film; cooling the stretched film to obtain a biaxially oriented super heat sealable polyethylene terephthalate film; The heat sealing temperature of the biaxially oriented super heat sealable polyethylene terephthalate film is 100°C to 200°C.

15. The method of claim 14, wherein the biaxially oriented super heat sealable polyethylene terephthalate film has at least two layers.

16. The method of claim 14, wherein preparing the heat sealable layer mixture comprises: charging terephthalic acid, dimethyl terephthalate, or a combination thereof, together with at least one diol and isophthalic acid into a reactor to obtain a reaction mixture; subjecting the reaction mixture to an esterification reaction at a temperature of 240° C. to 270° C. to obtain an esterified prepolymer; The esterified prepolymer is charged into a polycondensation reactor and one or more polycondensation catalysts selected from silica, antimony compounds and magnesium compounds are added; subjecting the prepolymer to a polycondensation reaction at a temperature in the range of 270° C. to 310° C. to obtain a molten amorphous polymer; cooling and processing the molten polymer to form chips or pellets; as well as The resulting chips are optionally subjected to solid state polymerization to obtain a heat sealable layer mixture comprising a heat sealable copolyester having an intrinsic viscosity greater than 0.65 dL / g.

17. The method of any one of claims 14-16, wherein the heat sealable copolyester comprises: 35 to 70 weight percent terephthalic acid, dimethyl terephthalate, or a combination thereof; 21 to 40 wt% of monoethylene glycol, diethylene glycol, triethylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, hexylene glycol, cyclohexanedimethanol, or a mixture of any two or more thereof; and 10 to 30 wt. % isophthalic acid.

18. The method according to any one of claims 14 to 17, wherein the core layer mixture comprises: 40 to 80 wt. % polyethylene terephthalate polyester; 0 to 30 wt. % fiber-grade polyester; 20 wt % to 100 wt % post-consumer recycled polyethylene terephthalate; and 0.05 to 0.1 wt% silica.

19. The method of any one of claims 14-18, wherein the polyethylene terephthalate polyester in the core layer mixture comprises 70 to 85 weight percent terephthalic acid, 20 to 30 weight percent monoethylene glycol, and 0.5 to 5 weight percent diethylene glycol.

20. The method of any one of claims 14-19, wherein the fiber-grade polyester in the core layer mixture comprises 65 to 85 weight percent terephthalic acid, 20 to 30 weight percent monoethylene glycol, and 2 to 10 weight percent diethylene glycol.

21. The method of claim 14, further comprising passing the molten first mixture and the molten second mixture through a filter.

22. The method of claim 14, further comprising laminating the molten first mixture and the molten second mixture together in a feedblock to create a laminated molten structure in the extrusion die.

23. The method of claim 14, wherein the processing comprises one or more of preheating, stretching, and cooling the extruded structure.

24. The method according to claim 23, wherein the stretching is performed sequentially or simultaneously in the machine direction and the transverse direction.

25. The method of claim 23, wherein the preheating, stretching, and cooling comprises machine direction preheating, stretching, and cooling followed by cross direction preheating, stretching, and cooling.

26. The method of claim 25, wherein the preheating conditions comprise passing the unstretched film through a machine direction preheating zone at a temperature of 70°C to 90°C, stretching the preheated structure in the longitudinal direction, and passing the longitudinally stretched film through a machine direction cooling zone at a temperature of 70°C to 90°C.

27. The method of claim 26, further comprising passing the cooled longitudinally stretched film through a transverse direction preheating zone having a temperature of 92°C to 110°C, stretching the preheated film in the transverse direction, and passing the transversely stretched film through a machine direction cooling zone having a temperature of 60°C to 85°C.

28. The method of any one of claims 14-27, further comprising adding an additional layer to the biaxially oriented super heat sealable polyester film.

29. The method of claim 28, wherein the additional layer comprises one or more of a sealant layer, a print layer, a metal layer, a barrier layer, an adhesive layer, a coating, a primer layer, and a protective layer.

30. A packaging material comprising a biaxially oriented super heat sealable polyester film produced by the method according to any one of claims 14 to 29.

31. A packaging material comprising the biaxially oriented super heat sealable polyester film according to any one of claims 1 to 10.

32. The packaging material according to claim 30 or 31, wherein the film is a food-grade packaging film or a medical product packaging film.

33. A method for preparing a heat-sealable copolyester composition, the method comprising: charging terephthalic acid, dimethyl terephthalate, or a combination thereof, together with at least one diol and isophthalic acid into a reactor to obtain a reaction mixture; subjecting the reaction mixture to an esterification reaction at a temperature of 240° C. to 270° C. to obtain an esterified prepolymer; charging the prepolymer into a polycondensation reactor and adding one or more polycondensation catalysts selected from silica, antimony compounds and magnesium compounds; subjecting the prepolymer to a polycondensation reaction at a temperature in the range of 270° C. to 310° C. to obtain a molten amorphous polymer; crystallizing the amorphous polymer at a temperature in the range of 110° C. to 170° C. to obtain chips or pellets having a crystallinity of about 40% or more; as well as The chips or pellets are optionally subjected to solid state polymerization to obtain a heat sealable layer mixture comprising a heat sealable copolyester having an intrinsic viscosity greater than 0.65 dL / g.

34. The method of claim 14 or 32, wherein the copolyester composition comprises a first polymer composition comprising pure terephthalic acid, ethylene glycol and isophthalic acid and a second polymer composition comprising pure terephthalic acid, ethylene glycol and neopentyl glycol, wherein the weight ratio of the first polymer composition to the second polymer composition is in the range of 70:

30.

35. The biaxially oriented super heat sealable polyester film according to any one of claims 1 to 9 or the multilayer high barrier film according to claim 11 or claim 12 for use in a bag or overwrap packaging.

Citation Information

Patent Citations

  • Biaxially stretched coextrusion sealable polyester film

    JP2001322220A